Elaboración de un protocolo y metodología de recolección de especies de hongos en frutos del componente florístico en el Bosque Siempre Verde Pie Montano (bspn01) de la cordillera occidental de los andes en el recinto los laureles entre el cantón pangua y la maná en el período 2019 - 2020 - Guevara Castillo, Katherine Adriana (2020)
In this research, the analysis of the bibliographic information of articles made in different sectors that contain similar characteristics to the study area was carried out. The objective of the research was to develop a protocol and methodology for the collection of fungal species in the fruits in floristic components, the study was developed in the Western Cordillera of the Andes in the Evergreen Pie Montano forest that is located in the Los Laurels between the canton Pangua and La Maná. Through bibliographic methodology, mechanisms were established that start from the area under study in order to isolate and cultivate the invasive fungi that Estrada and Ramírez in the General Mycology publication establish that they can be (Botrytis cinérea, Rhizopus and Mucor, Alternaria citri, Penicillium and Fusarium, Phytophthora infestans Oomycete), which depending on the environmental conditions can contaminate plants, producing diseases in the fruits in wild spies. An inductive and deductive methodology was used that goes from the particular to the general descriptive. The study area was delimited using the GIS software. Relevant information that allowed structuring a protocol with methodologies and techniques for collecting fungus in the field and laboratory, which will benefit researchers on practical work of these characteristics. In conclusion, the absence of data on the object of study within the country is a significant limitation, it is convenient to support research on natural resources and avoid forest loss, genetic that could lead to great scientific discoveries.